TRANSLATION SHIFT IN THE TRANSLATED NOVEL OF “TO KILL A MOCKINGBIRD” BY FEMMY SYAHRIANNI. - Dian Sukma Lestari (State University of Medan, 2018)
The aim of this study were to find out category shift types used in the translation of novel To Kill A Bird and to describe of how category shift is translated in the novel from English into Indonesian. This study were conducted by using descriptive qualitative method. The data of the study were words, phrases, and clauses in the novel To Kill A Mockingbird which is translated into Indonesian by Femmy Syahrianni. It was found that there were 280 data in the novel from English into Indonesian. The data analysis were taken by listing and bolding. Documentary sheets used as the instrument to collect the data. The data were analyzed based on Miles and Huberman (2014) by condensation which consists of selecting, focusing, simplifying, abstracting and transforming and then data display by using table in order to get easy analyzing the data. The result of this study were (1) there were four types of category shifts found in the novel To Kill a Mockingbird namely; structure shifts (36.78%), class shift (27.14%), unit shift (32.5%) and intra-system shift (3.27%). (2) The process of category shifts in the translation novel by having modifier-head in source language changed into head-modifier in target language, adverb in source language changed into verb in target language, one unit in source language changed into some units in target language. and plural in source language changed into singular in target language. Keyword: Translation shift, structure, class, unit, intra-system shift,novel.